Effect of water extract of meniran (Phyllanthus niruri L.) on toxic effect of aflatoxin B1 in liver of rats (Rattus norvegicus) (in Vivo) - Sri Suharmi Sri Suharmi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Phyllanthus niruri L. (meniran) is well known and can be used for traditional treatment of various diseases such as jaundice, diarrhea, and infection of tractus urinarius. The studies showed that the extract of Phyllanthus nirurl L. could be used as antihepatotoxics. This study was designed to investigate the effect of 10%, 20%. and 30% water-extract of Phyllanthus niruri L. herbs on the rats' liver treated with 15 ug aflatoxin 131 (AFB1) In 0,2 ml propylene glycol, orally by tube, everyday for 16 and 24 weeks. Employing the analysis variance, significant effect was observed in serum glutamate-pyruvate transaminase (SGPT) and liver's cytosol glutamate-pyruvate transaminase (GPT), but was not significant in liver's cytosol glutathione S-transferase (GST). However among inter group analysis, significant decrease in SGPT and liver's cytosol GPT observe only group treated with 20% water-extract of Phyllanthus niruri L. herbs and AFB1 compared to group treated with AFB1  (p<0,05). The study also demonstrated that 20% water-extract Phyllanthus niruri L. herbs could prevent metaplasia, hyperplasia, and proliferation of the bile duct epithellial cells and altered foci in the hepatocytes were caused by AFB1.Keyword : aflatoxin 131 - glutamate-pyruvate transaminase - glutathion S-transferase - Phyllanthus niruri L. - rat's liver